2016
DOI: 10.1017/jfm.2016.270
|View full text |Cite
|
Sign up to set email alerts
|

Microstreaming generated by two acoustically induced gas bubbles

Abstract: A theory is developed that describes microstreaming generated by two interacting gas bubbles in an acoustic field. The theory is used in numerical simulations to compare the characteristics of acoustic microstreaming at different frequencies, separation distances between the bubbles and bubble sizes. It is shown that the interaction of the bubbles leads to a considerable increase in the intensity of the velocity and stress fields of acoustic microstreaming if the bubbles are driven near the resonance frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…This is an expected result since both single-and double-bubble systems are driven in the same way and under the same experimental parameters. Therefore, although higher velocities are obtained in the double-bubble system, the flow strength is not increased, contrary to the theoretical result obtained by Doinikov & Bouakaz (2016). Consequently, no 544 R. Bolaños-Jiménez and others significant flow enhancement has been observed in this particular configuration of two bubbles.…”
Section: Two-bubble Systemcontrasting
confidence: 66%
See 3 more Smart Citations
“…This is an expected result since both single-and double-bubble systems are driven in the same way and under the same experimental parameters. Therefore, although higher velocities are obtained in the double-bubble system, the flow strength is not increased, contrary to the theoretical result obtained by Doinikov & Bouakaz (2016). Consequently, no 544 R. Bolaños-Jiménez and others significant flow enhancement has been observed in this particular configuration of two bubbles.…”
Section: Two-bubble Systemcontrasting
confidence: 66%
“…The reason for the flow enhancement is due to a better coupling between the volume and translational oscillation modes, reflected through a change in the phase shift of each of the bubbles. However, note that the configuration studied by Doinikov & Bouakaz (2016) is very different to ours: first, in their work, bubbles are freely suspended in the liquid (not attached to a wall). Secondly, bubbles respond to a plane travelling acoustic wave aligned with the bubbles' axis, so that the translational modes are also aligned with it.…”
Section: Two-bubble Systemmentioning
confidence: 74%
See 2 more Smart Citations
“…They also developed a theory for streaming near a bubble in the presence of a distant wall showing that presence of wall gives rise to higher acoustic streaming around the bubble (Doinikov and Bouakaz 2014). Doinikov and Bouakaz described the microstreaming generated by two interacting bubbles and showed that driving the bubbles at near resonance frequencies gives rise to higher microstreaming velocity and stresses (Doinikov and Bouakaz 2016). In addition to theoretical works to study the microstreaming flow field, there are experimental studies showing the flow field around a single and two oscillating bubbles resting on a solid surface (Collis, et al 2010, Thameem, et al 2016, Tho, et al 2007).…”
Section: Introductionmentioning
confidence: 99%